2009
DOI: 10.1136/ard.2008.101881
|View full text |Cite
|
Sign up to set email alerts
|

Human adipose-derived mesenchymal stem cells reduce inflammatory and T cell responses and induce regulatory T cells in vitro in rheumatoid arthritis

Abstract: The present work identifies hASCs as key regulators of immune tolerance, with the capacity to suppress T cell and inflammatory responses and to induce the generation/activation of antigen-specific regulatory T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
279
3
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(303 citation statements)
references
References 29 publications
15
279
3
6
Order By: Relevance
“…We recently described the immunosuppressive activity of human AD-MSCs in vitro on cells from RA patients (24). In the present study, we investigated the potential therapeutic action of human AD-MSCs in an experimental model of murine arthritis that shares a number of clinical, histologic, and immunologic features with RA.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…We recently described the immunosuppressive activity of human AD-MSCs in vitro on cells from RA patients (24). In the present study, we investigated the potential therapeutic action of human AD-MSCs in an experimental model of murine arthritis that shares a number of clinical, histologic, and immunologic features with RA.…”
Section: Resultsmentioning
confidence: 95%
“…Human AD-MSCs directly down-regulated the production of mediators of inflammation by activated synovial cells. Moreover, human AD-MSCs have been shown to inhibit the secretion of various inflammatory cytokines by monocytes isolated from RA patients and macrophages from mice with colitis (24,39). Several studies have also shown that BM-MSCs and AD-MSCs of murine origin are able to down-regulate systemic and local inflammatory responses (11,(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 2009 study Gonzalez-Rey et al [44] found that allogeneic ADSCs were able to suppress the antigen-specific response of T cells from patients with RA. Specifically, ADSC inhibited the proliferative response and the production of inflammatory cytokines by collagen-activated CD4 and CD8 T cells.…”
Section: Evidence For Adsc's Immunomodulatory Capacity: Cell Culture mentioning
confidence: 99%
“…[1][2][3][4] ASCs are a desirable therapeutic stem cell source as they are readily available, easily separated from liposuction aspirates or adipose tissue and can be propagated as needed in the laboratory. Data suggests that the therapeutic effects of ASCs are mediated in large part by release of paracrine factors that modulate inflammatory and immune responses or that enhance tissue repair.…”
Section: Introductionmentioning
confidence: 99%